2021
DOI: 10.1111/1346-8138.15792
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular large B‐cell lymphoma mimicking erythema nodosum: A case report and review of published works

Abstract: | e185LETTER TO THE EDITOR clinical courses have been reported in the English-language literature. [1][2][3][4][5] The clinical features of six cases including our case are summarized in Table S1. The average age at first visit was 60.3 years. Four cases had lesions limited to the lower legs and two cases had lesions distributed in the body area. The diagnosis of IVLBCL was made immediately after the first visit in two cases with long-lasting fever, whereas the other four cases were diagnosed as other diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The combination of fever of unknown origin with central nervous system symptoms, respiratory symptoms, or hepatosplenomegaly is a clue for suspecting IVLBCL in clinical settings. It has been reported that the development of neurological symptoms leads to the suspicion of IVLBCL in cases with cutaneous symptoms that were first considered and treated as other skin disorders 16 . Expansion of the knowledge of IVLBCL among clinicians may diminish the value of general symptoms in differentiating IVLBCL cases from IVLBCL‐suspected cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of fever of unknown origin with central nervous system symptoms, respiratory symptoms, or hepatosplenomegaly is a clue for suspecting IVLBCL in clinical settings. It has been reported that the development of neurological symptoms leads to the suspicion of IVLBCL in cases with cutaneous symptoms that were first considered and treated as other skin disorders 16 . Expansion of the knowledge of IVLBCL among clinicians may diminish the value of general symptoms in differentiating IVLBCL cases from IVLBCL‐suspected cases.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the development of neurological symptoms leads to the suspicion of IVLBCL in cases with cutaneous symptoms that were first considered and treated as other skin disorders. 16 Expansion of the knowledge of IVLBCL among clinicians may diminish the value The score of 0 or 1 indicates the low possibility of IVLBCL and random skin biopsies are not recommended. The score of 2 or 3 indicates the intermediate to high possibility of IVLBCL and random skin biopsies are recommended.…”
Section: Discussionmentioning
confidence: 99%